Use of a modified ureteral access sheath in semi-rigid ureteroscopy to treat large upper ureteral stones is associated with high stone free rates - Jad Khaled AlSmadi; Xiaohang Li; Guohua Zeng (Asian Journal of Urology)
Objective: To examine differences in outcomes of semi-rigid ureteroscopy (URS) with or without a modified-ureteral-access-sheath (mUAS) to treat large upper ureteral stones. Methods: Patients with single, radio-opaque large upper ureteral stone (≥10 mm) treated using semi-rigid URS between August 2013 and October 2016 were retrospectively evaluated. The stone-free status was determined from Kidney-ureter-bladder (KUB) X-ray films taken on postoperative Day 1 and after 1 month. Results: Of 103 patients meeting inclusion criteria, 43 (41.75%) and 60 (58.25%) were treated with semi-rigid URS with and without mUAS, respectively. The immediate stone-free rate (SFR) for the mUAS group was significantly higher than the non-mUAS group (40 [93.0%] vs. 46 [76.7%]; p = 0.033). The SFR at 1 month was also high for patients treated using mUAS, but not statistically different from patients not treated with mUAS (41 [95.3%] mUAS vs. 51 [85.0%] non-mUAS; p = 0.115). Auxiliary procedure rates were significantly lower for mUAS patients compared to non-mUAS patients (2 [4.7%] vs. 14 [23.3%]; p = 0.01). There were no significant differences in surgical duration and hospital stays, and the overall complication rates were statistically similar for mUAS patients compared to non-mUAS patients (1 [2.3%] vs. 3 [5.0%]; p = 0.638). Conclusion: Application of mUAS to treat large upper ureteric stones was associated with higher immediate SFR and final SFR, and lower auxiliary procedure rates relative to patients treated without use of mUAS. Moreover, the use of mUAS did not lengthen operation duration or hospital stays. Keywords: Ureteroscopy, Semi-rigid, Large ureteral stones, Ureteral access sheath, Modified ureteral access sheath